STRATEGI KOMUNIKASI INTERPERSONAL PENGELOLA GRUP PENJUALAN JERSEY DI FACEBOOK (STUDI KASUS BIT AND RUN PADA GRUP FACEBOOK LELANG JERSEY & AKSESORIS SEPAKBOLA DARI GO, PI, AAA ORIGINAL R7 GALLERY) - Meridian Firmansyah; Mariana Siregar; Qoute Nuraini (UNIVERSITAS PAKUAN, 2019)
ABSTRACT The aim of this research is to know the Interpersonal Communication Strategy of the Jersey Group Sales Manager on Facebook, a case study within the FacebookAuction Jersey Football Accessories from GO, PI, AAA-Original R7 Gallery. This research usedescriptive-qualitative method to describe how the interpersonal communication strategy use by group managers to minimize the number of bid and run actors. The results of this researchshow the connectionbetween the observations and the results of the in-depth interviews the author obtained from informant so expected to minimize the number of bid and run actors. The author analyzes the interpersonal communication strategy using social exchange theory in the form of rewards, costs, results and profits, the rate comparison shows the raw size (standard). The factors that determine the interpersonal communication strategy group manager are predictions based on psychological data, knowledge that explains, and the rules set out in private.. Keywords: communication strategy, bid and run, Facebook.